HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DENGAN KEMAMPUAN SERVIS PERMAINAN TENIS MEJA ATLET JUNIOR KLUB MANDIRI - Sari, Yulita Gumala; Ramadi, Ramadi; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is whether there is a correlation of handle establishment with ability of table game table services atlet junior klub Mandiri. The goal is to find out how big the handle establishment with ability of table game table services atlet junior klub mandiri singly. The technique of sampling performed with total sampling of 12 atlet junior klub Mandiri. This research using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, test of significance on the level of significance of Î± = 0.05. Test of normality of variabels X, L0maks (0,143) < Ltabel (0,242), and testing normality of variabels Y, L0maks (0,132) < Ltabel (0,242) in other words at a confidence level of 95% of normal data and concluded the results showed: where there is no relation between wrist and shoulder to service ability, with correlation r = 0.1559 where rhitung <rtabel 0,1559> 0,602. Thus, Ha is rejected..Key Word : correlation, handle establishment, ability of table game table services